(untitled) (World Bulletin of Education and Learning, 2026)
In the context of globalization, increasing intercultural interaction, and the multicultural nature of contemporary societies, the development of ethnocultural competence has become an essential component of teacher education. Future teachers are expected to possess not only professional knowledge and pedagogical skills but also the ability to understand, respect, and effectively interact with representatives of diverse cultural communities. The improved integrative-module methodology contributes significantly to the formation of ethnocultural competence among future teachers. Its implementation promotes intercultural dialogue, strengthens professional preparedness, and supports the development of culturally responsive educational practices in modern society.